2018
DOI: 10.1016/j.jaci.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reactions to therapeutic monoclonal antibodies: Phenotypes and endotypes

Abstract: HSRs to mAbs can be defined as type I, cytokine-release, mixed (type I/cytokine-release), and type IV reactions, which are identified by biomarkers such as skin test, tryptase, and IL-6. These phenotypes can be used to improve personalized and precision medicine when diagnosing HSRs to mAbs and providing management recommendations with desensitization. Desensitization provides a safe and effective retreatment option to remain on culprit mAbs as first-line therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
289
2
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(318 citation statements)
references
References 36 publications
7
289
2
20
Order By: Relevance
“…tion of infusion-related reactions is usually low grade 9 ; however, they may resemble allergic reactions. IgE-mediated HSR are still reported, which are confirmed by positive skin tests in nearly half of the cases 12,22. Unexpectedly, two patients exhibited anaphylaxis to rituximab at the 4th and 5th infusions, both of which necessitated use of epinephrine in our study.The local DHR reaction is another frequent adverse reaction, presenting at the injection site of subcutaneously administrated BD.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…tion of infusion-related reactions is usually low grade 9 ; however, they may resemble allergic reactions. IgE-mediated HSR are still reported, which are confirmed by positive skin tests in nearly half of the cases 12,22. Unexpectedly, two patients exhibited anaphylaxis to rituximab at the 4th and 5th infusions, both of which necessitated use of epinephrine in our study.The local DHR reaction is another frequent adverse reaction, presenting at the injection site of subcutaneously administrated BD.…”
supporting
confidence: 64%
“…The clinical picture of infusion-related and cytokine-release reactions includes fever, tachycardia, hypertension, dyspnea, nausea, vomiting, and syncope and usually occurs at first administration. 6 The frequency of hypersensitivity reactions varies according to the characteristics of the administered BD. Puxeddu et al have evaluated 671 patients who were treated with anti-TNF agents, and demonstrated that infliximab caused more severe and frequent allergic reactions (13.8%) than the other anti-TNF agents, etanercept (5.3%), and adalimumab (3.5%).…”
Section: Introductionmentioning
confidence: 99%
“…Even if HSRs to CZP are a quite rare occurrence (Isabwe et al, 2018), our case makes it advisable to administer at least the induction dose of the drug under medical supervision. Indeed, it is reported that AR to biologics is possible also after the first administration of the drug (Patel & Khan, 2017).…”
mentioning
confidence: 91%
“…Underlying pathogenic mechanism is not fully understood (de Las Vecillas Sánchez, Alenazy, Garcia‐Neuer, & Castells, ; Tétu et al, ). Although the Gell and Coombs classification has been useful to provide mechanistic understanding of HSRs, the classification and diagnosis of reactions to mAbs have provided a challenge (Isabwe, Garcia Neuer, de Las Vecillas Sanchez, Lynch, & Castells, ). HSRs to mAbs include acute infusion reactions (AIR) induced by cytokine release, besides Type I, Type III, and Type IV reactions (de Las Vecillas Sánchez et al, ; Tétu et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation